ADVOKASI KEPEMIMPINAN STRATEJIK DAN BUDAYA ORGANISASI UNTUK MENGURANGI PATOLOGI AROGANSI LEGISLATIF DAN SIKAP APATISME MASYARAKAT - Sugeng Rusmiwari; Annisa Purwatiningsih; Willy Tri Hardianto (Universitas Tribhuwana Tunggadewi, 2014)
In society there is always a person appointed or designated as a leader. Functions and duties of the leader is to move its leadership to reduce disease problems parse arrogance and apathy. Methods of research conducted by quantitative descriptive research, the primary data source is the primary data with data retrieval tool is a questionnaire or a questionnaire, which refers to the Likert Scale, the main data is supported by interviews and customized to the needs of field observations, sampling techniques used are sampled aims, analysis of data using path analysis. The results of the study, the first model of strategic leadership is able to reduce the arrogance and attitude of public apathy by 61.85%, while the second model with organization culture capable of reducing the arrogance and attitude of public apathy, amounting to 60.43%. So that the advocacy efforts of strategic leadership and organizational culture, and simultaneously convincing arrogant able to reduce the behavior and attitude of public apathy.